Optimizing Accounting Information Systems: The Critical Roles of User Involvement and Cloud Computing Integration in Bandung, Indonesia - Dzaky Cahaya Putra, Vicky; Revina Wigantini, Ghea (Journal of Accounting and Finance Management, 2025)
Information technology within a company plays a crucial role in providing timely and accurate information that aligns with the needs of managers in decision-making. The quality of an Accounting Information System is reflected in a system that successfully integrates all necessary elements and sub-elements to produce high-quality information. This study aims to assess the influence of User Involvement and Cloud Computing on the Quality of Accounting Information Systems (QAIS) in private national banks located in Bandung, Indonesia. The method used in this study is SEM (Structural Equation Model) with the PLS (Partial Least Square) approach. The research sample consists of 81 respondents from 14 private banks. The results reveal that User Involvement has a notable and substantial impact on the Quality of Accounting Information Systems, contributing 49.7%. User engagement in the development and utilization of accounting information systems is vital for improving system quality. Meanwhile, Cloud Computing also significantly influences QAIS, though its contribution is smaller at 5.3%. Both factors contribute significantly, thus, these findings provide important insights for banking management, highlighting that improving the quality of Accounting Information Systems relies not only on the adoption of advanced technology but also on maximizing user engagement.